Dendritic Cell Activation and Cytokine Production Induced by Group B Neisseria meningitidis: Interleukin-12 Production Depends on Lipopolysaccharide Expression in Intact Bacteria - Dixon, Garth L. J. (American Society for Microbiology, 2001)
Interactions between dendritic cells (DCs) and microbial pathogens are fundamental to the generation of innate and adaptive immune responses. Upon stimulation with bacteria or bacterial components such as lipopolysaccharide (LPS), immature DCs undergo a maturation process that involves expression of costimulatory molecules, HLA molecules, and cytokines and chemokines, thus providing critical signals for lymphocyte development and differentiation. In this study, we investigated the response of in vitro-generated human DCs to a serogroup B strain of Neisseria meningitidis compared to an isogenic mutant lpxA strain totally deficient in LPS and purified LPS from the same strain. We show that the parent strain, lpxA mutant, and meningococcal LPS all induce DC maturation as measured by increased surface expression of costimulatory molecules and HLA class I and II molecules. Both the parent and lpxA strains induced production of tumor necrosis factor alpha (TNF-α), interleukin-1α (IL-1α), and IL-6 in DCs, although the parent was the more potent stimulus. In contrast, high-level IL-12 production was only seen with the parent strain. Compared to intact bacteria, purified LPS was a very poor inducer of IL-1α, IL-6, and TNF-α production and induced no detectable IL-12. Addition of exogenous LPS to the lpxA strain only partially restored cytokine production and did not restore IL-12 production. These data show that non-LPS components of N. meningitidis induce DC maturation, but that LPS in the context of the intact bacterium is required for high-level cytokine production, especially that of IL-12. These findings may be useful in assessing components of N. meningitidis as potential vaccine candidates.